2021
DOI: 10.1371/journal.pone.0257062
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well-being and month-long LF/HF ratio among deskworkers

Abstract: The importance of workers’ well-being has been recognized in recent years. The assessment of well-being has been subjective, and few studies have sought potential biomarkers of well-being to date. This study examined the relationship between well-being and the LF/HF ratio, an index of heart rate variability that reflects sympathetic and parasympathetic nerve activity. Pulse waves were measured using photoplethysmography through a web camera attached to the computer used by each participant. The participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A significant negative correlation was observed between ⊿MCS and ⊿log LF/HF from T0 to T1. Prior research suggested that those with lower psychological well-being had higher LF/HF scores [ 37 ], and HF is associated with mental health-related indicators such as anxiety and depression [ 38 ]. Our results were consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…A significant negative correlation was observed between ⊿MCS and ⊿log LF/HF from T0 to T1. Prior research suggested that those with lower psychological well-being had higher LF/HF scores [ 37 ], and HF is associated with mental health-related indicators such as anxiety and depression [ 38 ]. Our results were consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, a spectral (or frequency domain) analysis of the HRV involves decomposing the signal into frequency bands and calculating the absolute power values in each band (Shaffer and Ginsberg 2017). The most common analysis using the frequency bands is based on the Low Frequency (LF)/High Frequency (HF) ratio -also called "balance" -which is used to reveal the amount of sympathovagal modulation of the heart rate (Shiga et al, 2021). In this analysis, a low LF/HF ratio reflects parasympathetic dominance that translates into self-regulating and self-soothing behaviours (Porges 2007), while a high LF/HF ratio indicates sympathetic dominance, which mediates arousal responses (Bootsma et al 1994) or an approach-motivated appetitive state (Shiota et al 2011).…”
Section: Psychophysiological Indicators and Field Data Collectionmentioning
confidence: 99%